The Nature of Ismail Zain’s Art: A Different Vision in Malaysian Contemporary Art - Issarezal Bin Ismail; Setiawan Sabana (Journal of Visual Art and Design, 2009)
This study is an exploration of Ismail Zain’s art, one of the pioneers in new media art in Malaysia. It will focus on his outstanding display in Digital Collage exhibition, an exhibition was notable by art critics from Malaysia and Asia Pacific as the touchstones of a new approach in art which was a non-personalized medium that specifically depended on highly mechanized consideration. The purpose of this study is to explore Ismail’s art in terms of the process itself. In order to understand the nature Ismail’s art, there are three important questions: What are the idea and concept in his art? What are the medium and technique that were used in his art? How was the artwork itself? These questions are addressed by data gathered in Malaysia through collection of the artifacts, documents regarding interviews, and some institutional historical resources. The data have been divided and presented into the following themes: (a) conception, (b) operations and (c) synthesis.